Mechanisms of oil pricing through SOMO and its impact on Iraqi oil exports - Baktyar Sabir Mohammed; Mohammad Shukri Mohammad Saeed; Idrees Sulaiman Abdullah (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
This study aimed to investigate the mechanisms used by the Iraqi State Oil Marketing Organization (SOMO) to set prices for its oil exports and to understand the impact of these prices on the volume of Iraqi oil exports. In order to achieve these objectives, the study analyzed data on SOMO’s pricing practices, market conditions, and oil export volumes over a specified period. The study found that the prices set by SOMO significantly affect the volume of Iraqi oil exports. Therefore, the research hypothesis was not fully proven as SOMO’s pricing strategies were found to be influenced by various factors rather than a clear and consistent marketing strategy. The study provides insight into the intricate process of oil pricing in Iraq and proposes that SOMO should develop a consistent marketing strategy to promote the value of high-quality Iraqi oils in the global market. The most important proposals of the study include identifying the various pricing strategies employed by SOMO, examining the factors that influence these pricing strategies, and highlighting the significant impact of SOMO’s pricing practices on the volume of Iraqi oil exports. This analysis provides insight into the intricate process of oil pricing in Iraq and the significance of SOMO’s role in shaping the nation’s oil exports, which could inform policy decisions related to energy policy, trade policy, and economic development.